STRUCTURAL, MAGNETIC AND ELECTRONIC PROPERTIES OF THE INTERMETALLIC COMPOUNDS FROM THE TERNARY SYSTEM Ce – Co – Mn - DUDRIC, R.; POPESCU, A.; ISNARD, O.; NEUMANN, M.; POP, V.; COLDEA, M. (Studia Universitatis Babeș-Bolyai Physica, 2015)
XRD, magnetic and XPS measurements of the three classes of intermetallic compounds with different crystallographic structures are reported. XPS spectra of Ce2Co15Mn3, CeCo7Mn5 and CeCo8Mn4 compounds pointed out the intermediate valence state of Ce atoms and that both Co and Mn atoms carry magnetic moments. The complex magnetic structure is determined by the competition between the ferromagnetic (Co–Co pairs) and antiferromagnetic (Co–Mn and Mn–Mn pairs) interactions. In CeCoMn, Ce3Co3Mn4 and Ce3Co6Mn compounds both Ce and Co atoms are non-magnetic like in the isostructural compound CeCo2. Magnetic behavior is mostly due to the Mn moments and depends essentially on the Mn - Mn distances.